Kompetensi Pedagogik dan Profesional Guru PAI dalam Penerapan Strategi Pembelajaran Pendidikan Agama Islam - Subairi, Agus; Karim, Nazir; Zaitun, Zaitun (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2024)
Abstract This research was carried out against the background of teachers' pedagogical and professional competence in implementing Islamic Religious Education learning strategies which include the subjects Al-Qur'an Hadith, Aqidah Akhlak, Fiqh, and History of Islamic Culture at the State Madrasah Tsanawiyah Siak Regency. This research aims to determine pedagogical competence and professional competence in determining and implementing learning strategies, strengthening the use of learning strategies and to find out ideal learning strategies and new learning strategies that can be applied to Islamic Religious Education at the Madrasah Tsanawiyah Negeri Siak Regency. This type of research is field research with a qualitative approach, and uses interviews, observation and documentation as data collection techniques. This research was conducted at Madrasah Tsanawiyah Negeri 1 Siak, Madrasah Tsanawiyah Negeri 2 Siak, and Madrasah Tsanawiyah Negeri 3 Siak. The results of the research are that teachers with pedagogical and professional competence have not yet determined learning strategies in preparing Learning Implementation Plans, teachers with high and very high pedagogical competence, quite high professional competence have implemented expository, inquiry, contextual learning strategies and independent learning strategies. However, it has not been maximized in utilizing strategies and methods according to teaching materials. The ideal learning strategy used in the learning process of Islamic religious education at Madrasah Tsanawiyah Negeri Siak Regency is expository and inquiry learning strategies according to the teacher's pedagogical and professional competence, and new learning strategies that can be applied. in learning Islamic religious education at Madrasah Tsanawiyah Negeri Siak Regency is a muhadharah learning strategy which is a habituation activity and is able to contribute to student learning outcomes covering the cognitive, affective and psychomotor domains. Keywords: Teacher Competencies, Learning Strategies, PAI Abstrak Penelitian ini dilaksanakan dengan latar belakang kompetensi pedagogik dan profesional guru dalam penerapan strategi pembelajaran Pendidikan Agama Islam yang meliputi mata pelajaran Al-Qur’an Hadits, Akidah Akhlak, Fiqih, dan Sejarah Kebudayaan Islam di Madrasah Tsanawiyah Negeri Kabupaten Siak. Penelitian ini bertujuan untuk mengetahui kompetensi pedagogik dan kompetensi professional dalam penetapan dan penerapan strategi pembelajaran, penguatan penggunaan strategi pembelajaran dan untuk mengetahui strategi pembelajaran ideal dan strategi pembelajaran baru yang dapat diterapkan pada Pendidikan Agama Islam di Madrasah Tsanawiyah Negeri Kabupaten Siak. Jenis penelitian ini adalah penelitian lapangan dengan pendekatan kualitatif, serta menggunakan wawancara, observasi, dan dokumentasi sebagai teknik pengumpulan data. Penelitian ini dilakukan di Madrasah Tsanawiyah Negeri 1 Siak, Madrasah Tsanawiyah Negeri 2 Siak, dan Madrasah Tsanawiyah Negeri 3 Siak. Hasil penelitian yaitu guru dengan kompetensi pedagogik dan professional yang dimiliki belum menetapkan strategi pembelajaran dalam penyusunan Rencana Pelaksanaan Pembelajaran, guru dengan kompetensi pedagogik yang tinggi dan sangat tinggi, kompetensi prosfesional yang cukup tinggi telah menerapkan strategi pembelajaran ekspositori, inkuiri, kontekstual, dan strategi pembelajaran mandiri, namun belum maksimal dalam memanfaatkan strategi dan metode sesuai materi ajar, strategi pembelajaran yang ideal digunakan pada proses pembelajaran pendidikan agama Islam di Madrasah Tsanawiyah Negeri Kabupaten Siak adalah strategi pembelajaran ekspositori dan inkuiri sesuai kompetensi pedagogik dan professional guru, dan strategi pembelajaran baru yang dapat diterapkan pada pembelajaran pendidikan agama Islam di Madrasah Tsanawiyah Negeri Kabupaten Siak adalah strategi pembelajaran muhadharah yang merupakan kegiatan pembiasaan dan mampu berkontribusi pada hasil belajar peserta didik meliputi ranah kognitif, afektif, dan psikomotorik. Kata Kunci: Kompetensi Guru, Strategi Pembelajaran, PAI.